Pengaruh Intensitas Komunikasi Penyuluh Terhadap Adopsi Petani dalam Program Sekolah Lapang Pengelolaan Tanaman Terpadu (SLPTT) Padi Sawah di Kecamatan Wawotobi Kabupaten Konawe - Isman Isman; Iskandar Zainuddin Rela; Salahuddin Salahuddin (Fakultas Pertanian Universitas Halu Oleo, 2021)
This study aimed to determine the effect of the intensity of the extension worker's communication on the adoption of farmers in the field school program for integrated crop management (SLPTT) for lowland rice in Wawotobi sub-district, Konawe district. The sampling technique used was purposive random sampling, and the data analysis used was descriptive and inferential statistics with simple linear regression. The research method used is a quantitative analysis method using primary data such as observations and questionnaires. The results of this studied indicate that the intensity of the extension worker's communication on farmer adoption in the field school program for integrated crop management (SLPTT) for lowland rice showed a positive and significant influence and contributes 32 ,8%. Regression equation X is obtained, which is = 37.502 = 0.367X, which means that the better the Intensity of Intensity of Communication for the Integrated Crop Management Field School Program (SLPTT), the higher the adoption of farmers in the program (SLPTT).